Doping Dependence Of Magnetic Susceptibility And Electrical Properties Of High Temperature Superconducting Ceramics - Mohamed, Syed Ali Beer (1999)

(untitled)
It has been well known that Bi-Sr-Ca-Cu-O system has three superconducting phases represented by general formula, Bi2Sr2Can-1CUnOy , referred to as 2201(n= 1,Tc~ 10K), 2212 (n=2, Tc~ 80K), and 2223 (n = 3, Tc~ 11 OK) The role of calcium and copper seem to influence the formation of those phases This research work was focussed at the role played by calcium in the formation of 2223 phase by doping this site with different elements having different valences and ionic radius Sample of Bi2-xbpxSr2Ca2Cu3O3(x=01 to 06)and Bi2Pb06Sr2Ca2-"MxCu3Oy (M = Ba, Y, V, Zn, Sn with x =0 02 to 0 10) were prepared using the conventional solid state reaction technique The samples were sintered at 855°C for 150 hours and annealed at 830°C for 30 hours The transport properties of the samples were measured using four-point probe resistance measurement, magnetic properties by using ac susceptibility, microstructure by scanning electron